2018
DOI: 10.1128/aem.00458-18
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Energy Conservation via Alternative Carbon Monoxide Metabolism in Carboxydothermus pertinax Revealed by Comparative Genome Analysis

Abstract: species are some of the most studied thermophilic carboxydotrophs. Their varied carboxydotrophic growth properties suggest distinct strategies for energy conservation via carbon monoxide (CO) metabolism. In this study, we used comparative genome analysis of the genus to show variations in the CO dehydrogenase-energy-converting hydrogenase gene cluster, which is responsible for CO metabolism with H production (hydrogenogenic CO metabolism). Indeed, the ability or inability to produce H with CO oxidation is expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Despite of its hydrogenogenic carboxydotrophy (Yoneda et al 2012 ), as per genome analysis, C. pertinax lacks genes encoding CODH-I catalytic subunit (CooS-I) and its transcriptional factor CooA-1 in their CODH-I−ECH gene cluster (Fukuyama et al 2017 ). Furthermore, gene expression analysis in C. pertinax has shown that genes encoding CODH-II catalytic subunit ( cooS - II ) and distantly encoding the ECH catalytic large and small subunits are remarkably upregulated under 100% CO, suggesting that C. pertinax performs hydrogenogenic CO metabolism in which CODH-II couples with distal ECH (Fukuyama et al 2018 ). Since C. pertinax possesses one CooA homolog (CooA-2) unlike C. hydrogenoformans possessing two CooA homologs, its transcriptional regulation from CO response is expected to be simpler than that of C. hydrogenoformans .…”
Section: Introductionmentioning
confidence: 99%
“…Despite of its hydrogenogenic carboxydotrophy (Yoneda et al 2012 ), as per genome analysis, C. pertinax lacks genes encoding CODH-I catalytic subunit (CooS-I) and its transcriptional factor CooA-1 in their CODH-I−ECH gene cluster (Fukuyama et al 2017 ). Furthermore, gene expression analysis in C. pertinax has shown that genes encoding CODH-II catalytic subunit ( cooS - II ) and distantly encoding the ECH catalytic large and small subunits are remarkably upregulated under 100% CO, suggesting that C. pertinax performs hydrogenogenic CO metabolism in which CODH-II couples with distal ECH (Fukuyama et al 2018 ). Since C. pertinax possesses one CooA homolog (CooA-2) unlike C. hydrogenoformans possessing two CooA homologs, its transcriptional regulation from CO response is expected to be simpler than that of C. hydrogenoformans .…”
Section: Introductionmentioning
confidence: 99%
“…The functions of these cooS genes have been predicted from their genomic contexts such as ECH, WLP, and ferredoxin-NAD(P)H oxidoreductase (Techtmann et al 2012;Inoue et al 2019), which are presumed to be regulated by CO-responsive transcription factors, such as CooA and RcoM (Shelver et al 1995;Komori et al 2007;Kerby et al 2008). However, recent studies of two hydrogenogenic carboxydotrophs, Carboxydothermus pertinax and Thermoanaerobacter kivui, show that the enzymatic coupling of cooS and ech genes that are distantly encoded in their respective genomes enables CO-dependent H 2 production (Fukuyama et al 2018(Fukuyama et al , 2019aSchoelmerich and Müller 2019). Moreover, cooS expression is upregulated in the presence of CO, despite the fact that no sequence motif is recognized by the CO-responsive transcriptional activator CooA in C. pertinax (Fukuyama et al 2018(Fukuyama et al , 2019a.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, recent studies of two hydrogenogenic carboxydotrophs, Carboxydothermus pertinax and Thermoanaerobacter kivui, show that the enzymatic coupling of cooS and ech genes that are distantly encoded in their respective genomes enables CO-dependent H 2 production (Fukuyama et al 2018(Fukuyama et al , 2019aSchoelmerich and Müller 2019). Moreover, cooS expression is upregulated in the presence of CO, despite the fact that no sequence motif is recognized by the CO-responsive transcriptional activator CooA in C. pertinax (Fukuyama et al 2018(Fukuyama et al , 2019a. Similarly, ech expression is upregulated in the presence of CO, although the genome does not encode any previously described COresponsive transcription factors in T. kivui (Schoelmerich and Müller 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations